Structural behavior of asphalt pavements - Sun, Lijun (Highway engineer) (Butterworth-Heinemann : Elsevier, 2016)
Structural Behavior of Asphalt Pavements provides engineers and researchers with a detailed guide to the structural behavioral dynamics of asphalt pavement including: pavement temperature distribution, mechanistic response of pavement structure under the application of heavy vehicles, distress mechanism of pavement, and pavement deterioration performance and dynamic equations. An authoritative guide for understanding the key mechanisms for creating longer lasting pavements, Structural Behavior of Asphalt Pavements describes the intrinsic consistency between macroscopic performance and microscopic response, structure and material, as well as global and local performances, and demonstrates the process of pavement analyses and designs, approaching science from empirical analyses. Analyzes the external and internal factors influencing pavement temperature field, and provide a review of existing pavement temperature prediction models Introduces a?Bridge Principleu0094 through which pavement performance and fatigue properties are consolidated Defines the intrinsic consistency between macroscopic performance and microscopic response, structure and material, as well as global and local performance Summaries the mechanistic response of pavement structure under the application of heavy vehicle, distress mechanism of pavement, pavement deterioration performance and dynamic equations, and life cycle analysis of pavement.